A water-based environmentally friendly anti-corrosion coating
By adding polyaniline intercalated graphene, composite nanoparticles and additives with corrosion inhibitors to the aqueous composite emulsion, a water-based environmentally friendly anticorrosion coating with long-term anticorrosion performance, low cost and environmentally friendly, solved the problems of insufficient anticorrosion performance and poor coating durability of existing water-based anticorrosion coatings.
Patent Information
- Application Number
- CN202310358313.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-06
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-04-06
AI Technical Summary
Existing water-based anticorrosion coatings have problems such as low solid content, single function, insufficient anticorrosion performance and poor coating durability, which is difficult to meet the working conditions requirements in complex environments.
Using aqueous composite emulsion as the matrix, polyaniline intercalated graphene, composite nanoparticles loaded with corrosion inhibitors, as well as additives, such as hydroxyethyl cellulose and expanded vermiculite powder, an environmentally friendly water-based environmentally friendly anticorrosion coating is prepared by ketoimine as a curing agent.
It improves the mechanical strength, corrosion resistance and durability of the coating, enhances the density and self-repairing performance of the coating, improves the anti-corrosion performance and self-cleaning ability, and meets the working conditions requirements in complex environments.
Smart Images

Figure BDA0004164071690000051 
Figure BDA0004164071690000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of anti-corrosion coatings, and in particular relates to a water-based environmentally friendly anti-corrosion coating. Background Art
[0002] Water-based anti-corrosion coatings are one of the current development directions of heavy-duty anti-corrosion coatings. They use water to replace organic solvents in traditional solvent-based coatings. They have the characteristics of low organic solvent volatility and environmental protection. However, due to various factors, the current usage ratio of water-based anti-corrosion coatings in my country is only about 10%. Therefore, research and development of water-based anti-corrosion coatings with high anti-corrosion performance has become a research trend in heavy-duty anti-corrosion coatings.
[0003] At present, the common water-based anti-corrosion coatings on the market include water-based acrylic coatings, water-based epoxy coatings, water-based inorganic zinc-rich coatings and water-based polyurethane coatings, etc. However, the current water-based anti-corrosion coatings have the following problems: First, the water-based anti-corrosion coatings have the problem of low solid content, which increases the production cost; second, the single-system anti-corrosion coatings have a single function and are difficult to meet the working conditions under complex environments; third, the anti-corrosion performance of the coatings needs to be improved, and the factors affecting the anti-corrosion performance such as the mechanical strength, density, and water resistance of the coating film need to be overcome;
[0004] Compared with traditional solvent-based coatings, water-based coatings have the advantages of low VOC content, convenient construction, easy cleaning, and green environmental protection. However, the existing water-based coatings contain polar channels formed by hydrophilic groups, which will accelerate the penetration of corrosive substances such as water, reducing the corrosion resistance and durability of the formed anti-corrosion coating.
[0005] In the prior art, inorganic particles are added to water-based paint to improve the wear resistance, aging resistance and corrosion resistance of the paint; however, inorganic particles have poor dispersibility in the paint matrix and are easy to agglomerate, which affects the interaction between the inorganic phase and the organic phase, resulting in poor coating film performance and failure to effectively improve the corrosion resistance; and the inorganic particles are prone to protective defects at the agglomeration site. Therefore, it is urgent to research and develop a water-based environmentally friendly anti-corrosion paint with long-term corrosion resistance, low cost, good corrosion resistance and environmental friendliness. Summary of the invention
[0006] In view of the deficiencies in the prior art, the purpose of the present invention is to provide an environmentally friendly, water-based, environmentally friendly anti-corrosion coating with long-term anti-corrosion performance, which solves the current problems of poor anti-corrosion performance and poor durability of the coating.
[0007] A water-based environmentally friendly anti-corrosion coating, comprising the following raw materials in parts by weight: 50-60 parts of water-based composite emulsion, 4-10 parts of ketimine; 4-6 parts of polyaniline intercalated graphene, 16-18 parts of composite nanoparticles loaded with corrosion inhibitors, and 5-10 parts of additives; the water-based composite emulsion is composed of sodium alginate / acrylic acid / acrylamide copolymer emulsion and water-based epoxy resin emulsion;
[0008] Preferably, the mass ratio of the sodium alginate, acrylic acid, acrylamide copolymer emulsion to the waterborne epoxy resin emulsion is 1:10;
[0009] Preferably, the composite nanoparticles are porous silica / titanium dioxide composite nanoparticles; the corrosion inhibitor is composed of histidine, anthocyanin and caffeic acid;
[0010] Furthermore, the method for preparing the aqueous composite emulsion is specifically as follows: preparing a sodium alginate solution, adding acrylamide and acrylic acid thereto to obtain a mixed solution, introducing nitrogen thereto, and then sequentially adding ammonium persulfate and ethylenediamine to react to obtain a sodium alginate / acrylic acid / acrylamide copolymer emulsion; adding the sodium alginate / acrylic acid / acrylamide copolymer emulsion to an aqueous epoxy resin emulsion, and then adding microcrystalline cellulose thereto and stirring evenly to obtain an aqueous composite emulsion;
[0011] Preferably, the amount of microcrystalline cellulose added is 10% by weight of the aqueous composite emulsion;
[0012] Preferably, the waterborne epoxy resin is E44;
[0013] Furthermore, the preparation method of the polyaniline intercalated graphene oxide is specifically as follows: dispersing graphene oxide in a hydrochloric acid solution of tyrosine, uniformly dispersing by ultrasonication, adding aniline and ammonium persulfate thereto, and polymerizing under ice-salt bath conditions to obtain the polyaniline intercalated graphene oxide;
[0014] Preferably, the weight ratio of the graphene oxide to aniline is 6:1; the molar ratio of aniline to ammonium persulfate is 0.5:1;
[0015] Preferably, the preparation method of the composite nanoparticles loaded with corrosion inhibitor is as follows: tetrabutyl titanate and tetraethyl silicate are dispersed in a mixed solution of alcohol and glacial acetic acid to obtain a mixed dispersion after uniform dispersion; Fe 3+ with Fe 2+Dissolve in deionized water, add Fe powder thereto, add the above-mentioned mixed dispersion thereto under 55°C water bath conditions; at the same time, adjust the pH of the system to be alkaline; then heat to 80°C, add sodium citrate solution, continue stirring the reaction until completion, and obtain magnetic composite nanoparticles after magnetic separation; soak the magnetic composite nanoparticles in a hydrochloric acid solution, filter and wash until the solution does not contain iron ions, disperse the nanoparticles in a corrosion inhibitor solution, and obtain composite nanoparticles loaded with corrosion inhibitors after ultrasonic treatment;
[0016] Preferably, the reaction system contains tetrabutyl titanate, tetraethyl silicate, Fe 3+ , Fe 2+ The molar ratio of is 3:6:1:0.5; the corrosion inhibitor solution is obtained by dispersing histidine, anthocyanin and caffeic acid in water at a weight ratio of 2:1:1;
[0017] Furthermore, the auxiliary agent comprises hydroxyethyl cellulose and expanded vermiculite powder;
[0018] The present invention uses an aqueous composite emulsion as a matrix, adds polyaniline intercalated graphene, composite nanoparticles loaded with a corrosion inhibitor and an auxiliary agent thereto; uses ketimine as a curing agent to prepare an environmentally friendly, water-based environmentally friendly anticorrosive coating with long-term anticorrosive performance.
[0019] The water-based environmentally friendly anti-corrosion coating disclosed by the present invention uses sodium alginate / acrylic acid / acrylamide copolymer and water-based epoxy resin as coating matrix, and the presence of sodium alginate enhances the film-forming property of the coating matrix; in the sodium alginate / acrylic acid / acrylamide copolymer, the sodium alginate is not polymerized, and runs through the acrylic acid / acrylamide polymer in a chain structure, thereby improving the elasticity of the polymer material; the copolymer and the water-based epoxy resin are composited to effectively improve the adhesion of the coating, and at the same time, the copolymer has swelling properties, and can swell when the coating is defective after long-term physical action, thereby improving the compactness and self-healing property of the coating; adding composite nanoparticles loaded with corrosion inhibitors and polyaniline intercalated graphene to the matrix can effectively improve the mechanical strength, corrosion resistance and durability of the coating; the composite nanoparticles loaded with corrosion inhibitors The particles significantly reduce the secondary agglomeration of nanoparticles in the coating matrix and enhance the dispersibility of composite nanoparticles in the coating; the corrosion inhibitor molecules are gradually released in the nanopowder as the environmental conditions change, significantly improving the corrosion durability; the composite nanoparticles have a skeleton effect in the coating, significantly improving the mechanical strength of the coating; polyaniline intercalated graphene oxide improves the dispersibility of graphene sheets in the water-based epoxy resin matrix, effectively avoiding the stacking of graphene sheets; polyaniline and epoxy resin are chemically bonded; at the same time, there is a π-π effect between aniline and graphene, and the presence of aniline enhances the dispersibility and binding stability of graphene in the epoxy resin matrix, and the stably dispersed lamellar graphene effectively blocks the invasion of small molecules in the channel formed by the water-containing polar groups; and reduces the probability of small molecule corrosion. The three work together to form the water-based environmentally friendly anti-corrosion coating of the present invention with good film coating, strong mechanical strength, good density and excellent anti-corrosion performance.
[0020] In the present invention, hydroxyethyl cellulose and expanded vermiculite powder are added as auxiliary agents. Hydroxyethyl cellulose has a thickening effect and improves the coating performance of the coating. Vermiculite has a lamellar structure, and polymer molecules in the coating matrix will penetrate into the vermiculite lamellar structure. Vermiculite serves as a connecting point between polymer molecules, thereby improving the mechanical strength of the coating film; at the same time, the density of the coating is also improved.
[0021] Beneficial Effects
[0022] The water-based environmentally friendly anti-corrosion coating of the present invention has good storage stability compared to existing water-based anti-corrosion coatings, and the coating has good mechanical strength, is resistant to chemical corrosion such as light, acid and alkali, and has a self-healing effect after physical damage, showing long-term anti-corrosion performance and good self-cleaning ability; it effectively improves the problem of unsatisfactory anti-corrosion performance caused by poor mechanical strength, density and water resistance of existing water-based coatings. DETAILED DESCRIPTION
[0023] The technical solution of the present invention is described in detail below in conjunction with specific embodiments.
[0024] Raw material preparation
[0025] (1) Preparation of aqueous composite emulsion
[0026] A sodium alginate solution with a mass percentage concentration of 1-2% is prepared, acrylamide and acrylic acid are added thereto to obtain a mixed solution, and after nitrogen is introduced, ammonium persulfate and ethylenediamine are added in sequence to react to obtain a sodium alginate / acrylic acid / acrylamide copolymer emulsion;
[0027] A sodium alginate / acrylic acid / acrylamide copolymer emulsion is added to a 10-fold weight of an aqueous epoxy resin (E44) emulsion to obtain a mixed solution, and microcrystalline cellulose (microcrystalline cellulose accounts for 10% of the total weight of the mixed solution) is added to the mixed solution and stirred evenly to obtain an aqueous composite emulsion; wherein the weight ratio of the sodium alginate, acrylamide, and acrylic acid is 1:1:3; the amount of ammonium persulfate added is 0.1wt% of the total weight of acrylic acid and acrylamide; and the amount of ethylenediamine added is 0.15wt% of the total weight of acrylic acid and acrylamide.
[0028] (2) Preparation of polyaniline intercalated graphene
[0029] Graphene oxide is dispersed in a hydrochloric acid solution of tyrosine with a volume (mass) twice that of tyrosine, and after being uniformly dispersed by ultrasonication, aniline and ammonium persulfate are added thereto, and polymerized under ice-salt bath conditions to obtain polyaniline intercalated graphene oxide; wherein the weight ratio of the graphene oxide to the aniline is 6:1; and the molar ratio of the aniline to the ammonium persulfate is 0.5:1.
[0030] (3) Preparation of composite nanoparticles loaded with corrosion inhibitors
[0031] Preparation of corrosion inhibitor solution: Disperse histidine, anthocyanin and caffeic acid in water at a weight ratio of 2:1:1. Preparation of composite nanoparticles loaded with corrosion inhibitor:
[0032] Tetrabutyl titanate and tetraethyl silicate are dispersed in a mixed solution of alcohol and glacial acetic acid to obtain a mixed dispersion after uniform dispersion; Fe 3+ with Fe 2+ The invention discloses a method for preparing a nanoparticle-containing composite material comprising the steps of: dissolving the nanoparticle in deionized water, adding Fe powder thereto, and adding the above-mentioned mixed dispersion thereto under 55°C water bath conditions; adjusting the pH value of the system to 9-10; heating the system to 80°C, adding sodium citrate solution, and continuing to stir the reaction until completion, and obtaining magnetic composite nanoparticles after magnetic separation; soaking the magnetic composite nanoparticles in a hydrochloric acid solution, filtering and washing the solution until no iron ions are contained therein, dispersing the nanoparticles in a corrosion inhibitor solution, and obtaining composite nanoparticles loaded with corrosion inhibitors after ultrasonic treatment; wherein the reaction system contains tetrabutyl titanate, tetraethyl silicate, and Fe 3+ , Fe2+ The molar ratio is 3:6:1:0.5.
[0033] Example 1
[0034] A water-based environmentally friendly anti-corrosion coating comprises the following raw materials in parts by weight: 50 parts of water-based composite emulsion, 4 parts of ketimine, 4 parts of polyaniline intercalated graphene, 16 parts of composite nanoparticles loaded with corrosion inhibitors, and 5 parts of additives; wherein the additives are composed of hydroxyethyl cellulose and expanded vermiculite powder in a weight ratio of 5:1;
[0035] Example 2
[0036] A water-based environmentally friendly anti-corrosion coating comprises the following raw materials in parts by weight: 55 parts of water-based composite emulsion, 7 parts of ketimine, 5 parts of polyaniline intercalated graphene, 17 parts of composite nanoparticles loaded with corrosion inhibitors, and 7.5 parts of additives; the additives are composed of hydroxyethyl cellulose and expanded vermiculite powder in a weight ratio of 5:1;
[0037] Example 3
[0038] A water-based environmentally friendly anti-corrosion coating comprises the following raw materials in parts by weight: 60 parts of water-based composite emulsion, 10 parts of ketimine, 6 parts of polyaniline intercalated graphene, 18 parts of composite nanoparticles loaded with corrosion inhibitors, and 10 parts of additives; the additives are composed of hydroxyethyl cellulose and expanded vermiculite powder in a weight ratio of 5:1;
[0039] Comparative Example 1
[0040] The raw material composition of the water-based anticorrosive coating in Comparative Example 1 is substantially the same as that in Example 2, except that the water-based composite emulsion is replaced by an equal amount of water-based epoxy resin emulsion (E44);
[0041] Comparative Example 2
[0042] The raw material composition of the water-based anticorrosive coating of Comparative Example 2 is substantially the same as that of Example 2, except that the polyaniline intercalated graphene is replaced by an equal amount of graphene;
[0043] Comparative Example 3
[0044] The raw material composition of the water-based anticorrosive coating in Comparative Example 3 is substantially the same as that in Example 2, except that the composite nanoparticles loaded with the corrosion inhibitor are replaced with an equal amount of composite nanoparticles;
[0045] Comparative Example 4
[0046] The raw material composition of the water-based anticorrosive coating in Comparative Example 4 is substantially the same as that in Example 2, except that the additive does not contain expanded vermiculite powder;
[0047] The properties of the coatings prepared in Examples 1-3 and Comparative Examples 1-4 of the present invention were tested, and the detection method was based on the water-based epoxy resin inspection standard (HG / T4759-2014); the test results are shown in Table 1.
[0048] Table 1
[0049]
[0050]
[0051] It can be seen from the data in Table 1 that the water-based environmentally friendly anti-corrosion coating of the present invention has good stability and anti-corrosion performance, and meets the requirements of water-based epoxy resin coatings.
[0052] From the comparison of the test results of Example 2 and Comparative Examples 1-4 in Table 1, it can be seen that the sodium alginate / acrylic acid / acrylamide copolymer, polyaniline intercalated graphene oxide, composite nanoparticles loaded with corrosion inhibitors and expanded vermiculite in the additives of the present invention have a significant effect on the anti-corrosion performance of the coating; the raw materials of the coating of the present invention have a synergistic effect in ensuring the performance of the coating.
[0053] Compared with Example 2, the coating matrix of Comparative Example 1 does not contain sodium alginate / acrylic acid / acrylamide copolymer, the adhesion between the coating and the matrix is reduced, and the impact resistance, acid, alkali, water, salt spray and moisture and heat resistance are reduced; the reason may be that the addition of sodium alginate / acrylic acid / acrylamide copolymer as a matrix helps to improve the viscoelasticity of the coating and improve the adhesion of the coating. At the same time, it chemically bonds with the water-based epoxy resin and fills the molecular layers of the epoxy resin, and has swelling characteristics, which effectively alleviates the problem of the polar channels formed by hydrophilic groups having poor barrier capacity for small molecules such as inorganic acids and alkalis and water molecules; and gives the coating the ability to self-repair, thereby improving the corrosion resistance of the coating.
[0054] In comparative example 2, the impact resistance and corrosion resistance of the coating obtained by replacing the polyaniline intercalated graphene oxide in the coating with an equal amount of graphene are reduced; the polyaniline intercalated graphene promotes the dispersion of graphene in the coating matrix, and can exist chemical bonding with the coating matrix, thereby improving the density of the coating matrix and avoiding protection defects; the stably dispersed lamellar graphene effectively blocks the invasion of small molecules in the channels formed by water-containing polar groups and causes corrosion; and significantly improves the corrosion resistance of the coating.
[0055] In comparative example 3, the composite nanoparticles loaded with corrosion inhibitor in the coating are replaced with an equal amount of composite nanoparticles. The composite nanoparticles have poor stability in the coating matrix and are prone to secondary aggregation, which causes the coating to agglomerate. At the same time, the anti-corrosion performance of the formed coating is also significantly reduced. However, the dispersibility of the composite nanoparticles loaded with corrosion inhibitor in the coating matrix is significantly improved, and the secondary agglomeration of the composite nanoparticles is effectively avoided; agglomeration in the coating and the occurrence of uneven coating problems are prevented; and as the environmental conditions change, the corrosion inhibitor molecules are released, effectively improving the anti-corrosion performance of the coating.
[0056] In Comparative Example 4, no expanded vermiculite powder was added to the coating additive, and the anti-corrosion performance of the coating was reduced. The reason may be that no vermiculite was added, the density and mechanical strength of the coating were reduced, the polymer molecules in the coating matrix would penetrate into the vermiculite lamellar structure, and vermiculite, as the connection point between polymer molecules, could improve the mechanical strength of the coating; at the same time, it could also improve the density of the coating and improve the anti-corrosion performance.
[0057] In summary, the raw materials in the water-based anti-corrosion coating of the present invention interact with each other to form a water-based anti-corrosion coating with good chemical stability, good anti-corrosion performance and long durability.
[0058] The above embodiments are only preferred specific implementation methods of the present invention, and the protection scope of the present invention is not limited thereto. Any simple changes or equivalent replacements of the technical solutions that can be obviously obtained by any technician familiar with the technical field within the technical scope disclosed in the present invention all fall within the protection scope of the present invention.
Claims
1. A water-based environmentally friendly anti-corrosion coating, characterized in that: The invention comprises the following raw materials in parts by weight: 50-60 parts of aqueous composite emulsion, 4-10 parts of ketimine, 4-6 parts of polyaniline intercalated graphene, 16-18 parts of composite nanoparticles loaded with corrosion inhibitors, and 5-10 parts of auxiliary agents; the composite nanoparticles are porous silica / titanium dioxide composite nanoparticles; the corrosion inhibitor is composed of histidine, anthocyanin and caffeic acid; the auxiliary agents include hydroxyethyl cellulose and expanded vermiculite powder; The method for preparing the aqueous composite emulsion specifically comprises: preparing a sodium alginate solution, adding acrylamide and acrylic acid thereto to obtain a mixed solution, introducing nitrogen thereto, and then sequentially adding ammonium persulfate and ethylenediamine to react to obtain a sodium alginate / acrylic acid / acrylamide copolymer emulsion; adding the sodium alginate / acrylic acid / acrylamide copolymer emulsion to an aqueous epoxy resin emulsion, and then adding microcrystalline cellulose thereto and stirring evenly to obtain an aqueous composite emulsion; The preparation method of the composite nanoparticles loaded with corrosion inhibitors is specifically as follows: tetrabutyl titanate and tetraethyl silicate are dispersed in a mixed solution of alcohol and glacial acetic acid to obtain a mixed dispersion after uniform dispersion; Fe 3+ with Fe 2+ Dissolve in deionized water, add Fe powder, add the above mixed dispersion in a 55°C water bath, and adjust the pH of the system to alkaline; The temperature was then raised to 80 °C, sodium citrate solution was added, and the reaction was continued to be stirred until completion, and magnetic composite nanoparticles were obtained after magnetic separation; the magnetic composite nanoparticles were immersed in a hydrochloric acid solution, filtered and washed until the solution did not contain iron ions, and the nanoparticles were dispersed in a corrosion inhibitor solution, and composite nanoparticles loaded with corrosion inhibitors were obtained after ultrasonic treatment; wherein tetrabutyl titanate, tetraethyl silicate, Fe 3+ , Fe 2+ The molar ratio is 3:6:1:0.5; the corrosion inhibitor solution is obtained by dispersing histidine, anthocyanin and caffeic acid in water in a weight ratio of 2:1:
1.
2. The water-based environmentally friendly anti-corrosion coating according to claim 1, characterized in that: The mass ratio of the sodium alginate, acrylic acid, acrylamide copolymer emulsion to the waterborne epoxy resin emulsion is 1:
10.
3. The water-based environmentally friendly anti-corrosion coating according to claim 1, characterized in that: The added amount of the microcrystalline cellulose is 10% by weight of the aqueous composite emulsion.
4. The water-based environmentally friendly anti-corrosion coating according to claim 1, characterized in that: The preparation method of the polyaniline intercalated graphene oxide is specifically as follows: graphene oxide is dispersed in a hydrochloric acid solution of tyrosine, and after being uniformly dispersed by ultrasonication, aniline and ammonium persulfate are added thereto, and the polyaniline intercalated graphene oxide is polymerized under ice-salt bath conditions to obtain the polyaniline intercalated graphene oxide.
5. The water-based environmentally friendly anti-corrosion coating according to claim 4, characterized in that: The weight ratio of the graphene oxide to aniline is 6:1; the molar ratio of the aniline to ammonium persulfate is 0.5:1.
Citation Information
Patent Citations
Preparation method of graphene-polyaniline supercapacitor electrode material
CN105513818A
Magnetic sewage treatment agent and preparation method thereof
CN109761331A
Steel structure anti-corrosion coating
CN110218504A
Non-toxic environment-friendly water-based paint and preparation method thereof
CN112080181A
Preparation method of inorganic oxide pigment and filler loaded with composite corrosion inhibitor
CN113462199A
Cited By
Water-based environment-friendly emulsion and application thereof in real stone paint coating
CN120424541A